Continuing a community of practice beyond the death of its domain: examining the Tales of Link subreddit. Issue 1 (2nd January 2022) - Britt, Brian C.; Britt, Rebecca K.; Hayes, Jameson L.; Oh, Jeyoung
ABSTRACT: Communities of practice (COPs) have become increasingly important across a wide range of casual and business contexts, including innovative technical product development, refining skill sets for competitions, or establishing corporate strategies. Members of such communities forge interpersonal relationships and develop sophisticated practices around a shared domain, either interdependently contributing to a joint product or advancing as individuals. However, prior research has not examined attempts to sustain a COP whose domain has been terminated. Such cases have become increasingly common, especially as COPs emerge around ephemeral media products such as mobile games. A recent example, Tales of Link, based on the popular 'Tales of' Japanese role-playing game series, shut down on March 2018, but members of the subreddit devoted to it have attempted to keep the community active. As such, a computational text analysis of 33, 476 comments and 1, 000 posts on the r/talesoflink subreddit was conducted to assess how community members attempt to sustain COPs beyond the lifespan of their original domains. The findings offer insight into the discourse within COPs, the strategies and success rates of survival that may vary by such organisations, conversations surrounding the ever-changing gacha game model, and the potential changes in members' messages and behaviours.